The Effect of HCl Concentration on The Activation of Bentonite as A Catalyst in The Pyrolysis Process of Polypropylene (PP) Plastic Waste at The Integrated Waste Management Facility of Asari Cilegon - Suhendi, Endang; Heriyanto, Heri; Anam, Muhammad Khoirul; Aulia, Anida; Putri, Rizki Amalia; Wardalia, Wardalia (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2024)
Pyrolysis is the process of heating a substance without the presence of oxygen, causing the decomposition of plastic materials (polymers). Pyrolysis is used as an alternative to reduce the amount of plastic which is a source of environmental problems. This research aimed to determine the effect of HCl concentration on bentonite catalyst activation on the liquid product yield of pyrolysis of polypropylene (PP) plastic waste and to determine the characteristics of the liquid pyrolysis products. This research was carried out in several stages including raw material preparation, catalyst activation, and pyrolysis process. In bentonite catalyst activation, the HCl concentration was varied to 0.25, 0.50, and 0.75 M. The results showed that the highest liquid product yield was obtained at a concentration of 0.50 M, namely 76% with a product density range of 0.7452-0.762 g/ml. The heating value of the liquid product at 0.50 M HCl activated bentonite was 6806.48 cal/g. Through GC-MS analysis, the liquid product contained 2,4-Dimethyl-1-heptene with an area of 8.21% and a retention time of 3.626. Based on XRD analysis, the bentonite contained minerals of montmorillonite, kaolinite, and quartz.